2003
DOI: 10.1016/s0019-1035(03)00086-1
|View full text |Cite
|
Sign up to set email alerts
|

HST observation of the atmospheric composition of Jupiter’s equatorial region: evidence for tropospheric C2H2☆

Abstract: This paper presents the first detailed analysis of acetylene absorption features observed longward of 190.0 nm in a jovian spectrum by the Faint Object Spectrograph on board the Hubble Space Telescope. The presence of two features located near 207.0 nm can only be explained by a substantial abundance of acetylene in the upper troposphere. Using a Rayleigh-Raman radiative transfer model, it was determined that the acetylene vertical profile is characterized by a decrease in the mole fraction with increasing pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 49 publications
2
14
0
1
Order By: Relevance
“…c d e f Fouchet et al 115 Edgington et al 104 Lara et al 126 Edgington et al 103 Carlson et al 136 Griffith et al 137 Irwin et al 138 de Pater et al 109 Folkner et al 118 Gibson et al 114 Burgdorf et al 139 Achterberg et al 140 Betremieux et al 133 Sromovsky et al 117 The larger optical depth leads to increased shielding of the NH 3 , with a corresponding slight reduction in the NH 2 production rate at the base of the NH 3 cloud and a very slight increase in the NH 3 mole fraction at the top of the cloud. This change in optical depth in the 300-700 mbar pressure region has almost no effect on species abundances, except for that of N 2 , whose production rate slightly drops.…”
Section: Photochemical Model Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…c d e f Fouchet et al 115 Edgington et al 104 Lara et al 126 Edgington et al 103 Carlson et al 136 Griffith et al 137 Irwin et al 138 de Pater et al 109 Folkner et al 118 Gibson et al 114 Burgdorf et al 139 Achterberg et al 140 Betremieux et al 133 Sromovsky et al 117 The larger optical depth leads to increased shielding of the NH 3 , with a corresponding slight reduction in the NH 2 production rate at the base of the NH 3 cloud and a very slight increase in the NH 3 mole fraction at the top of the cloud. This change in optical depth in the 300-700 mbar pressure region has almost no effect on species abundances, except for that of N 2 , whose production rate slightly drops.…”
Section: Photochemical Model Resultsmentioning
confidence: 99%
“…The HST/FOS ultraviolet spectra are affected by scattering and absorption from many gas-phase and aerosol species, all of which have poorly constrained parameters. Both NH 3 and C 2 H 2 are clearly detected in the HST/FOS ultraviolet spectra, 132,133 but deriving mole fractions from the spectra may be problematic. The strongest argument against the 1.5 × 10 −7 tropospheric C 2 H 2 mole fraction derived by Bétrémieux et al 133 is that such a large amount would generate absorption wings around observed mid-infrared C 2 H 2 emission lines, which Bétrémieux et al recognize is inconsistent with their own ground-based infrared data, 133 as well as with other mid-infrared observations.…”
Section: Photochemical Hcn Source and The Tropospheric C 2 H 2 Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…A subset of the HST FOS data-set was re-visited by Bétrémieux et al (2003). Their modelling required an ethane abundance of 150 ppb at 120 to 300 mbar in the upper troposphere, disagreeing with previous measurements in the ultraviolet (see Table 1) and disagreeing with observations in the mid-infrared.…”
Section: Introductionmentioning
confidence: 95%
“…Here, we describe the development of our radiative transfer code to be able to model and retrieve atmospheric abundances from ultraviolet reflectance spectra. We then apply this model to observations of Jupiter by the Cassini Ultraviolet Imaging Spectrograph (UVIS), comparing them to results derived from mid-infrared observations acquired HST 10-30 Bétrémieux et al (2003) HST 40…”
Section: Introductionmentioning
confidence: 99%